2021
DOI: 10.1182/blood.2021011121
|View full text |Cite
|
Sign up to set email alerts
|

Clonal hematopoiesis in sickle cell disease

Abstract: and the staff of the cellular biology laboratory for excellent technical assistance. The authors also thank the French Intergroup for Myeloproliferative neoplasms for insightful discussions. L.B. is a "CCA-INSERM Bettencourt," an "Association Laurette Fugain," a "F ederation Leuc emie Espoir," an "Oncosph ere-Pfizer," and an LNCC grant recipient, a "GILEAD hematology/oncology international research scholar," and an "EHA physician-scientist" grant recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
(32 reference statements)
1
19
0
Order By: Relevance
“…CH is an important factor predisposing to myeloid malignancies and it has been speculated that individuals with SCD may have elevated rates of CH (20). A preliminary study even reported an observed, albeit slight, increase in CH in people with SCD within a pilot cohort in comparison to external controls (21).…”
Section: Discussionmentioning
confidence: 93%
“…CH is an important factor predisposing to myeloid malignancies and it has been speculated that individuals with SCD may have elevated rates of CH (20). A preliminary study even reported an observed, albeit slight, increase in CH in people with SCD within a pilot cohort in comparison to external controls (21).…”
Section: Discussionmentioning
confidence: 93%
“…While whole genome sequencing did not show an increased prevalence in CH [ 64 ], deeper whole exome sequencing revealed a higher prevalence of CH in patients with SCD compared to healthy controls [ 2 ]. Though the relative risk of leukemia is higher in individuals with SCD, the absolute risk is low.…”
Section: Discussionmentioning
confidence: 99%
“…To assess CH at a deeper level, Pincez et al assessed whole exome sequencing data from 1459 patients with SCD and 6848 African-American controls; 517 had sickle cell trait [ 2 ]. Variant allele frequency ranged from 2.5 to 26%, with a median of 7%.…”
Section: Clonal Hematopoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…One study ( 18 ) analyzed CH in whole-exome sequencing data from 1,459 patients with SCD using an adjacent set of 6,848 African Americans as a comparator. In this study, subjects were considered to have CH if they had an alteration in any of 46 handpicked genes with VAF greater than or equal to 2% and less than 40%.…”
Section: Incidence Of Ch In Scdmentioning
confidence: 99%